(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Communicative Language Teaching (CLT) represents a cornerstone in contemporary foreign language pedagogy, shifting the focus from grammatical accuracy to functional communicative competence. This thesis delves deeper into the efficacy of CLT by examining its theoretical underpinnings, empirical validations, contextual adaptations, and persistent challenges. Drawing on a synthesis of global research from 2020-2025 and Uzbekistan-specific studies, it highlights CLT’s role in enhancing speaking skills, motivation, and cultural awareness among learners. Key findings reveal significant improvements in communicative proficiency through interactive tasks, though implementation barriers like resource limitations and cultural mismatches in regions such as Uzbekistan necessitate tailored integrations with traditional methods. The analysis advocates for hybrid approaches and technology-enhanced CLT to address 21st-century educational demands, offering insights for policymakers and educators in diverse linguistic landscapes.